Particle Swarm Optimization for photovoltaic model identification - Nunes, Hugo (2020)
This paper proposes a comprehensive modeling and parameters extraction method of solar photovoltaic module based on the Particle Swarm Optimization algorithm. The character-istic curves of photovoltaic panel are obtained by using only the information provided by the manufacturer data-sheet, avoiding the need to carry out experimental data. The performance and the accuracy of the proposed method are evaluated by applying the one-diode model and the results are compared with those obtained by the well-known Lambert W function. The proposed method shows a higher performance.